Modeling Si/SiGe/Si Quantum Well Solar Cell Using Different Well Width and Mole Fraction - Raden Arief Setyawan (Jurnal EECCIS (Electrics, Electronics, Communications, Controls, Informatics, Systems), 2007)
Quantum Well Solar Cell ( QWSC) was proposed as a means to achieve higher efficiencies compare with conventional monolithic solar cell structures. Quantum well formed by adding lower band gap material within intrinsic region of p-i-n solar cell with less than 100 Aï‚° thicknesses. In this research, five structure of QWSC device were designed with different quantum well thickness. Each structure using different SiGe mole fraction in order to achieve the influence of mole fraction variation to quantum efficiency (QE). Parameters of SiGe in simulations were obtained from various references to use with PC1D and Simwin Software. From simulation result, quantum efficiency will increase from mole fraction 0.2 (84.5135 %) until reaching maximum efficiency at mole fraction 0.75 (91.5703 %). Quantum efficiency begin to decrease at mole fraction higher than 0.75. At mole fraction 0.85 quantum efficiency equal to 90.4830 % and at mole fraction 0.95 quantum efficiency sharply become 71.6327 %.